Embedding the integrated assessment of agricultural systems in a companion modeling process to debate and enhance their sustainability - Hossard, Laure; Tardivo, Caroline; Barbier, Jean Marc; Cittadini, Roberto; Delmotte, Sylvestre; Le Page, Christophe (Springer Nature, 2022)
The Companion Modeling approach aims to stimulate learning and sharing of perceptions among several actors through the co-construction and use of a model, while the Integrated Assessment of Agricultural Systems aims to assess a large set of performances of current and alternative systems. Our research question was: to what extent does the joint use of these two methods foster sustainability thinking? We show how the co-design of evolving agriculture scenarios and the use of Integrated Assessment of Agricultural Systems methods guided the implementation of a Companion Modeling process applied to the Valensole Plateau, southeastern France. An initial phase, based on a preliminary diagnosis, aimed to collectively formulate the issues to be addressed, and to engage the actors in a collective dynamic. The second phase consisted of leading actors in the co-construction of a simulation model to represent the agricultural system to be evaluated using economic, social, and environmental indicators at different scales. In the final phase, the current situation and the co-designed scenario were collectively analyzed. The scenario was conceived as a “worst case”, embedded with drivers such as input costs and climate change. Opposing adaptation strategies were envisioned by farmers and other actors. Results show how debates between participants adaptively shaped the model. Scenario simulations highlighted better environmental performance at the expense of economic performance. The differences between farms led to discussions on technical management. Overall, the process stimulated collective reflection among the actors and created a learning experience with the sharing of perceptions and knowledge about the agricultural system. The model was considered relevant by the participants, who expressed interest in continuing its exploration. Our approach, which used a unique combination of Integrated Assessment of Agricultural Systems and scenario development with Companion Modeling, could be adapted to other areas and issues, although tool transfer remains an open question.